2016
DOI: 10.1097/nmd.0000000000000557
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a Low-Support Cognitive Remediation Training Program for Psychosis

Abstract: Cognitive remediation (CR) has emerged as the treatment of choice for impaired cognition in psychosis. However, little is known about adherence rates and factors predicting adherence to CR, particularly in clinical settings where high-level therapist support is unavailable. This study aimed to establish adherence rates and examine variables predicting adherence to a computerized CR program for psychosis (with minimal support). Patients with psychosis (n = 61) participated in an 8-week CR program. Results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
2
9
1
1
Order By: Relevance
“…Of the participants in our study, a half of the sample did not engage with at least one third of the sessions of CRT. Nevertheless, these rates are similar to those in previously published studies from other groups ( 58 ). This fact may be influenced by the study design because we included a randomized phase and half of the patients received TAU.…”
Section: Discussionsupporting
confidence: 92%
“…Of the participants in our study, a half of the sample did not engage with at least one third of the sessions of CRT. Nevertheless, these rates are similar to those in previously published studies from other groups ( 58 ). This fact may be influenced by the study design because we included a randomized phase and half of the patients received TAU.…”
Section: Discussionsupporting
confidence: 92%
“…First, results showed a satisfactory adherence rate, with almost 70% of the participants completing the entire course of the protocol and adhering to over 80% of the prescribed sessions and outcome measures, suggesting that subjects did not seem to find the time commitment, the assessments, or the training burdensome. These completion rates are comparable with some studies (15,(28)(29)(30) and in contrast with other ones conducted so far (31), showing a higher attrition rate. Nevertheless, the present study adopted several measures to sustain adherence, mostly by strengthening the relationship with the therapist that has been shown to have a fundamental role in ensuring participants' completion of the training modules (32) and providing social cues to improve patients' self-esteem and motivation, supporting the use of strategies, motivation, or reinforcement and helping to develop metacognition, which is thought to be a key component for improving transfer from cognitive change to functional development (33,34).…”
Section: Discussionsupporting
confidence: 90%
“…Remote treatment delivery can be easily accessed from clients' homes and may encourage treatment adherence for individuals who have motivational impairments ( Jimenez et al, 2019 ). Conversely, while specific motivational impairments are associated with treatment disengagement, past research has also demonstrated that those with higher negative symptom profiles may have greater adherence to CR programs ( Dillon et al, 2016 ), supporting the notion that there may be a specific symptom profile of individuals who may benefit most from CR. Furthermore, cognitive impairments themselves may also impede therapeutic engagement and attendance while participating in CR (e.g.…”
Section: Introductionmentioning
confidence: 91%